Epidemiological overview of brain neoplasms with surgical treatment in a third level hospital - Meza-García, Carlos Francisco (Universidad de Sonora, 2022)
Introduction: The overall incidence rate of primary tumors of the central nervous system is 10.8 per 100,000 people per year. Objective: To describe the epidemiological picture of patients with encephalic neoplasms who underwent surgery in the year 2017 to July 2018 in a tertiary care level hospital. Methodology: Descriptive, observational, cross-sectional and retrolective study. As inclusion criteria, the clinical records of the files of people over 18 years of age with a diagnosis of EN who received neurosurgical treatment during the aforementioned period were used. The elimination criteria were clinical records related to spinal surgery and duplicate records. The study adhered to the Code of Ethics of the World Medical Association and the Declaration of Helsinki. It was approved by the institution's ethics and research ethics committees. Results: The average age found in the records was 49.315 years, 89.8% of encephalic neoplasms were of primary origin in people aged 48.715.9 years. The most frequent with 42% were gliomas and 29.5% were meningiomas. Most of them were located in the brain with 39%. The most frequent surgical procedure performed was supratentorial craniotomy in 69.3%, the most common tumor was encephalic in 38.6% and almost 70% were malignant tumors. Conclusion: the epidemiological overview is the first step for the integration of proposals for nursing clinical practice guidelines and care plans, mainly at in-hospital and out-of-hospital discharge.